Jens Chr. Birch og Henrik Christoffersen (red.), Citizen Participation and Local Government in America and Denmark. Gentofte: Eriling Olsens Forlag, 1981, 219 s., 70,00 kr. - Gundelach, Peter (Politica, 1982)
-